Primary Care Physicians' Knowledge, Perceptions, and Comfort Level in Managing Patients Fasting in Ramadan - Hayam Hamodat; Saif Syed; Malik Ali; Yaeesh Sardiwalla; Fatima Imran; Ameer Jarrar; Farina Rafiq; Khader Zimmo; Mohamed Eissa; Babar Haroon (SAGE Publishing, 2020)
Background: Once a year, Muslims fast from dawn to sunset during the month of Ramadan. While fasting has many positive health implications, it may pose risks to individuals with underlying health issues. Despite the exemption from fasting for those who are ill, many Muslims with chronic conditions choose to fast. It is unclear how many Muslim patients receive counseling on fasting. As such, the purpose of this pilot project was to assess the knowledge, perception, and comfort level of primary care physicians (PCPs) at Dalhousie University's Department of Family Medicine in managing patients choosing to fast during Ramadan. Methods: A 16-item anonymous, self-administered, structured online survey was distributed to PCPs with an academic affiliation with the Department of Family Medicine at Dalhousie University. Participants rated their level of comfort, objective knowledge, and perceptions of managing patients fasting in Ramadan. Results: Many PCPs perceived the importance of understanding Ramadan fasting and its relevance to their patients' health, however, they did not have adequate knowledge about the matter. The majority of PCPs felt they received inadequate training in this area and did not feel comfortable counseling and managing the health of these patients. Conclusions: The findings of this study have outlined a knowledge gap that exists within our PCP community and will help inform and prioritize educational needs and direct efforts to ensure safe patient management during Ramadan.